Combination of adjuvant chemotherapy and radiotherapy is associated with improved survival at early stage type II endometrial cancer and carcinosarcoma. (18th February 2016) - Sozen, Hamdullah; Çiftçi, Rumeysa; Vatansever, Dogan; Topuz, Samet; Iyibozkurt, Ahmet Cem; Bozbey, Hamza Ugur; Yaşa, Cenk; Çali, Halime; Yavuz, Ekrem; Kucucuk, Seden; Aydiner, Adnan; Salihoglu, Yavuz
Abstract : Aims: The aim of this study was to describe the impact of postoperative adjuvant treatment modalities and identify risk factors associated with recurrence and survival rates in women diagnosed with early stage type II endometrial cancer and carcinosarcoma. Methods: In this retrospective study, patients diagnosed with early stage (stages I‐II) carcinosarcoma and type II endometrial cancer were reviewed. All women underwent comprehensive surgical staging. Postoperative treatment options of chemotherapy (CT), radiotherapy (RT), observation (OBS) and chemotherapy–radiotherapy (CT‐RT) combination were compared in terms of recurrence and survival outcome. Results: In CT‐RT treatment arm, recurrence rate was found as 12.5% and this result is significantly lower than the other treatment approaches ( P = 0.01 CT alone: 33.3%, RT alone: 26.7%, OBS: 62.5%). Three‐year disease free survival(DFS) rate and overall survival (OS) rate were statistically higher for the group of women treated with combination of CT‐RT (92–95%) compared to the women treated with RT alone (65–72%), treated with CT alone (67–74%) and women who received no adjuvant therapy (38–45%). The multivariate analysis revealed that carcinosarcoma histology was associated with shortened DFS and OS ( P = 0.001, P = 0.002). On the other hand, being at stage Ia ( P = 0.01, P = 0.04) and receiving adjuvant treatment of CT‐RT combination ( P = 0.005, P = 0.002) appeared to lead to increased DFS and OS rates. Conclusions: We identified that a combination treatment of chemotherapy and radiotherapy is superior compared to other postoperative adjuvant treatment approaches concerning PFS, OS and recurrence rates in stages I‐II of type II endometrial cancers and uterine carcinosarcoma.